Исторические и медико – гигиенические аспекты возникновения и развития виноградарства и виноградолечения в Мелитопольском уезде Таврической губернии - Резник, В.И. (Культура народов Причерноморья, 2003)
It highlights the little know facts of the indefatigable and productive activity of Andrej Korvatskij, a regional doctor of Melitopol district in the XIX century, a founder of intensive, experimental and industrial vine-growing in Melitopol district, a discoverer of deep artesian wells, an author of the conception of population health studying and desease prophylaxis.
It presents the basic data as for Korvatskij’s achievements in flying and sliding sands exploitation in the way of planting of aclimatized West-European sorts of fruit-trees and vine there.
It reveals his role in the improvement of the steep dweller’s nourishment, the wide inclusion of fruit and grapes into his ration.
It analyses Korvatskij’s experience as for the introduction and wide application of grape treatment in Priazov steppe.